Negotiating access - Uhnoo, Sara (Courtroom ethnography, 2023)
Research access in ethnographic studies “involves gaining permission to conduct research in a particular social setting” (Shaffir and Stebbins in B.W. Shaffir and R.A. Stebbins (eds.) Experience fieldwork. An inside view of qualitative research, Sage, London, 1991, 25). Following laws about public transparency, courts are normally open to the public. This is however not the case for all courts or all types of trials. In many jurisdictions, judges may use discretion to exclude spectators from court hearings, including researchers. As this chapter will show, this and other aspects may turn access into a complicated phase in courthouse ethnography. If access to the field is denied, it will delay the data collection, it may require adaptation of the research design, and in the worst case it may jeopardise the realisation of an entire study. In this chapter, we describe and reflect upon how we negotiated and gained access to Swedish rape hearings. Three different access strategies are described and the importance of judges as gatekeepers is illustrated with quotes taken from our fieldnotes. We conclude the chapter by summarising our lessons learned and practical guidance and top tips for ethnographic researchers.